2019
DOI: 10.1186/s12891-019-2918-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychological factors outmatched morphological markers in predicting limitations in activities of daily living and participation in patients with lumbar stenosis

Abstract: BackgroundRecent demographic changes have led to a large population of older adults, many of whom experience degenerative disc diseases. Degenerative lumbar spinal stenosis (DLSS) is associated with considerable discomfort and limitations in activities of daily living (ADL). Symptomatic DLSS is one of the most frequent indications for spinal surgery. The aim of this study was to identify sociodemographic variables, morphological markers, depression as well as fear of movement that predict ADL performance and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The somatic focus subscale of the Tampa Scale of Kinesiophobia (TSK) was strongly and positively correlated with the RehaCAT lower extremity subscale while the activity avoidance subscale was moderately and positively correlated with the RehaCAT lower extremity subscale. The score of the RehaCAT activities of daily living subscale was moderately and positively correlated with the somatic focus and the activity avoidance subscales of the TSK (21). The correlation between daily step count and kinesiophobia was not significant (35).…”
Section: Physical and Psychological Factors Associated With Functional Tasks Promsmentioning
confidence: 84%
See 3 more Smart Citations
“…The somatic focus subscale of the Tampa Scale of Kinesiophobia (TSK) was strongly and positively correlated with the RehaCAT lower extremity subscale while the activity avoidance subscale was moderately and positively correlated with the RehaCAT lower extremity subscale. The score of the RehaCAT activities of daily living subscale was moderately and positively correlated with the somatic focus and the activity avoidance subscales of the TSK (21). The correlation between daily step count and kinesiophobia was not significant (35).…”
Section: Physical and Psychological Factors Associated With Functional Tasks Promsmentioning
confidence: 84%
“…Depression, Anxiety, and Fear Avoidance. Two studies reported on the association between either depression or fear avoidance and functional tasks (21,35). Depression was strongly and negatively correlated with the patient's participation in social, daily and work-related activities using the Aachen Activity and Participation Index (AAPI).…”
Section: Physical and Psychological Factors Associated With Functional Tasks Promsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lumbar spinal stenosis (LSS) is one of the most frequent causes of low back pain and leg numbness while moving 1 . The symptoms adversely affect the health-related quality of life (HRQoL) and activities of daily living (ADL) of older adults 2,3 ; however, a well-known feature of LSS is symptom relief with rest or when sitting down 4,5 .…”
Section: Introductionmentioning
confidence: 99%